The introduction of the international normalized ratio as a breakthrough event in the history of thrombosis - Armando Tripodi (Bleeding, Thrombosis and Vascular Biology)
Very few among the youngest readers of this Journal would think about the introduction of the international normalized ratio (INR) as a breakthrough event in the history of thrombosis...